Perancangan Desain User Interface dan User Experience pada STIKI PMB Online dengan Menggunakan Metode User-Centered Design - Setiawan, Rosandi Fila; Widodo, Sugeng; Zulkarnain, Adnan (LPPM STIKI MALANG, 2021)
PMB STIKI Online uses the website as a medium to provide information related to lectures at STIKI Malang. The development of a website must go through several usability guidelines to ensure that the website's goals can be achieved. The research approach is carried out using User-centered Design by involving the user in the design process to produce a website that is acceptable to the user. STIKI PMB Online has never been evaluated before in relation to complaints from prospective students about the difficulty of finding the information they want to obtain. The problems contained in STIKI PMB Online are expected to be resolved in the design solutions that will be carried out. This study discusses starting from the determination of the context of use and specifications of user needs, problem analysis, design of solution designs, and design evaluation result. The results of this study indicate that the problems that occur can be resolved with the design rules contained in the usability standardization.